PENETAPAN KADAR ZAT AKTIF N,N-DIETHYL-METATOLUAMIDE (DEET) DALAM PRODUK SOFFELL SPRAY LOKAL DAN EKSPOR SECARA KROMATOGRAFI GAS - Renny Futeri; Olga Zalona Illahi (Politeknik ATI Padang, 2019)
Soffell is a mosquito repellent product in the form of lotions and sprays. Soffell can be used to protect the body from mosquito bites with an effective protection of up to 8 hours because it contains DEET in it. Determination of the level of DEET active substances in Soffell Spray products used the gas chromatography method. Gas chromatography is a method of separating a mixture into its constituent components based on the interaction of the stationary phase and the mobile phase. The stationary phase used is the dimethyl polysiloxane column while the mobile phase is N2 gas. N2 gas used because it is inert (does not react with analytes) is also easily obtained and inexpensive. In this gas chromatography, the column used is the RTX-1 column which contains dimethyl polysiloxane. The injection system used is a split injector for samples that have high concentrations. The incoming sample volume is only what is needed while the remainder is discarded. The detector used is FID (Flame Ionization Detector) so it requires H2 gas as a combustion gas and O2 as an oxidizer to produce a flame. DEET active substances levels obtained from Soffell Spray products are Soffell Spray Geranium 12.815 %, 12.518 %, 12.543 % and Floral Spray 11.900 %, 12.043 %, 12.067 % respectively. The analysis results obtained from Soffell Spray products are still included in the standard company specifications are for Soffell Geranium Flowers 11.97-13.78 % and Floral Spray 11.05-12.72 %.